Development, Safety, and Efficacy of Janus Kinase Inhibitors in Rheumatoid Arthritis - Lederman, Lynne (MD Conference Express, 2013)
The four Janus kinases (JAKs), JAK1, JAK2, JAK3, and Tyk2, are essential components of the signaling pathway of certain cytokines [O'Shea JJ et al. N Engl J Med 2013]. This article reviews the role of JAKs in inflammation and JAK inhibitor efficacy and toxicity, the clinical data for tofacitinib, as well as discusses kinase inhibition in development, baricitinib, which strongly inhibits JAK1 and JAK2.